2020
DOI: 10.3390/coatings10040349
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superhydrophobic and UV-Resistant Silk Fabrics with Laundering Durability and Chemical Stabilities

Abstract: To obtain a superhydrophobic surface, SiO2 nanoparticles are deposited on the surface of silk fabric (SF) by Plasma Enhanced Chemical Vapor Deposition (PECVD) to form a hierarchical roughness structure. In addition, a durable superhydrophobic SiO2@silk fabric was further prepared by hexamethyldisilazane (HMDS) modification. Compared with bare silk, the surfaces of the SiO2@silk fabric exhibit higher surface roughness and excellent superhydrophobic activity, with a contact angle (CA) of ~152°. The excellent UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CVD mainly uses one or several vapor compounds or elements containing thin-film elements to chemically react together on the surface of substrate to produce a thin film [45,125]. Commonly used deposition materials include carbon nanotubes [126,127], SiO 2 [128,129], TiO 2 [130], PDMS [131,132] and so on. For example, Tombesi et al [133] used aerosol-assisted chemical vapor deposition (AACVD) to fabricate SiO 2 nano-particle films with dual-scale roughness on glass substrates.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…CVD mainly uses one or several vapor compounds or elements containing thin-film elements to chemically react together on the surface of substrate to produce a thin film [45,125]. Commonly used deposition materials include carbon nanotubes [126,127], SiO 2 [128,129], TiO 2 [130], PDMS [131,132] and so on. For example, Tombesi et al [133] used aerosol-assisted chemical vapor deposition (AACVD) to fabricate SiO 2 nano-particle films with dual-scale roughness on glass substrates.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…The color strength ( K / S value) under illuminant D65 were automatically calculated 47 . The ultraviolet protection factor (UPF), ultraviolet transmittance rates T UVA , T UVB was measured using UV‐912E tester (Wenzhou Da Rong Textile Instrument Co., Ltd., China) 2,48 . The stress–strain curves of the untreated and modified silk fabrics (2 cm × 10 cm) were measured three time on electromechanical universal testing machine (CMT4304, MTS SYSTEMS CO, LTD, China) to attain the average value with a gauge length of 100 mm and a strain rate of 10 mm/min under the condition of 20°C and 40% RH.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…47 The ultraviolet protection factor (UPF), ultraviolet transmittance rates T UVA , T UVB was measured using UV-912E tester (Wenzhou Da Rong Textile Instrument Co., Ltd., China). 2,48 The stress-strain curves of the untreated and modified silk fabrics (2 cm  10 cm) were measured three time on electromechanical universal testing machine (CMT4304, MTS SYSTEMS CO, LTD, China) to attain the average value with a gauge length of 100 mm and a strain rate of 10 mm/min under the condition of 20 C and 40% RH. The light, washing and rubbing fastness of dyed silk fabrics were tested according to GB/T 8427-2008, ISO 105-C06, and ISO 105-X12, respectively.…”
Section: Properties Measurementsmentioning
confidence: 99%
“…For several decades, many researchers have tried to understand the UV-induced photo-aging process of silk fabrics, solutions, and films. The accumulated results have demonstrated that SF fiber is susceptible to UV-induced changes in color and brightness [ 10 , 11 ] because SF molecules contain numerous aromatic amino acids such as tyrosine (5.1%), tryptophan (0.1%), and phenylalanine (0.4%) [ 8 ]. In addition, it is revealed that photo-destruction of the ordered structures by UV irradiation makes silk fibers more brittle than those that are nontreated [ 12 ].…”
Section: Introductionmentioning
confidence: 99%